Multi-System Inflammatory Syndrome in Children (MIS-C) Reported in COVID-19 Positive 2.5-Year Old Boy - Alyousef, Ammar Muhammad; Alshamrani, Mohammad Abdulkhaliq; Alruwaili, Abdulaziz Sayah; Aldmak, Amer Farhan; Okash, Waleed Ahmad (International Journal of Innovative Research in Medical Science, 2020)
Multi-System Inflammatory Syndrome in Children (MIS-C) has been recently described as a newly emerging serious condition linked to COVID-19. We, hereby, describe and report the clinico-laboratory characteristics of a 2.5-year-old boy who tested positive for SARS-CoV2 and exhibited an image of MIS-C. We seriously want to spotlight this new entity in Saudi Arabia where the peak of SARS-CoV2 is descending whereas MIS-C case might be increasing. The same scenario had occurred in other countries. We recommend reporting possible cases of MIS-C to our local, state, or territorial health department. We expect increased reporting cases of COVID-19-associated MIS-C in Saudi Arabia and Arabian Gulf region.